Kewajiban Human Rights Due Diligence Bagi Perusahaan Dalam Kerangka Environmental Social Governance Di Indonesia - Almer, Muhammad Almer Levaryan; Syahrul Sajidin (RechtJiva, 2026)
The implementation of Environmental, Social, and Governance (ESG) principles in Indonesia, particularly concerning Human Rights protection, faces significant challenges due to the absence of binding regulations. Current regulations, such as Presidential Regulation No. 60 of 2023, remain voluntary and serve merely as strategic guidelines, proving ineffective in preventing corporate human rights violations or providing remedies for victims. This research aims to analyze the urgency of regulating Human Rights Due Diligence (HRDD) obligations and formulate an ideal legal framework using a normative juridical method with a comparative approach to Germany’s Lieferkettensorgfaltspflichtengesetz (LkSG). The findings confirm that transitioning to a mandatory regime is critical on philosophical, juridical, and sociological grounds to address the current legal vacuum. This study proposes a statutory framework requiring companies to implement comprehensive human rights risk management, ranging from identification to remediation. This formulation must include strict sanctions, such as administrative fines based on profit percentages and business license suspensions. This legislative step is crucial not only for ensuring human rights protection and legal certainty.